2018
DOI: 10.1177/0897190018779847
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Feasibility of Implementing a Systematic Approach for Medication Therapy Management in the Community Pharmacy Setting: A Pilot Study

Abstract: Implementing this systematic approach to providing MTM into the pharmacy workflow may lead to an improvement in CMR completion rate. However, the sample size is small, and the results and process may not be generalizable to other sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…With their dedication to medication surveillance, pharmacists are leading candidates to manage requesting of PGx testing, recording of PGx results and application of the PGx guidelines. This is confirmed by other pilot studies performed in pharmacy settings [31,32,33,34,35]. However, we found that both pharmacists and GPs are very able to record PGx results in their EMRs as contra-indications (96% and 33% of pharmacists and GPs, respectively); enabling deployment of relevant guidelines by the clinical decision support system when a drug-gene interaction is encountered both at prescribing and dispensing.…”
Section: Discussionsupporting
confidence: 85%
“…With their dedication to medication surveillance, pharmacists are leading candidates to manage requesting of PGx testing, recording of PGx results and application of the PGx guidelines. This is confirmed by other pilot studies performed in pharmacy settings [31,32,33,34,35]. However, we found that both pharmacists and GPs are very able to record PGx results in their EMRs as contra-indications (96% and 33% of pharmacists and GPs, respectively); enabling deployment of relevant guidelines by the clinical decision support system when a drug-gene interaction is encountered both at prescribing and dispensing.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, economic evaluation of clinical pharmacy services has been promoted since the late 1990s 62 , 63 and positive economic benefits as a result of pharmacists’ interventions and services have been reported. 64 Among the great challenges to improving the quality of healthcare despite limited healthcare resources, economic outcomes are an increasingly substantive focus among healthcare policy-makers, consumers, and payers during their decision-making process with regard to identifying the most cost-effective healthcare interventions and developing reasonable remuneration mechanisms for the professional services provided. 65 67 To be able to achieve a sustainable development of pharmacists’ interventions in COPD management, there needs to be a reasonable remuneration system for which economic indicators about the pharmacists’ intervention, such as reductions in direct costs, unscheduled hospital days, or total treatment costs, would be highly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shed light on the progressive multifactorial problems, that were facing the vast majority of asthma patients around the world, several studies that were carried out to address asthma therapy related problems, such as controllers under prescribing, quick-reliever overusing, poor inhaling technique and medication non-compliance, furthermore, patients' poor perception of their disease [4,5]. Thus, various approaches to asthmatic care are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Long term medication management services, which are provided to asthmatic patients have achieved and maintained significant improvements and significant decrease in the overall asthma-related costs, although medications' high costs, this is due to increased adherence and use [4,5]. Medication Adherence is a critical base for a successful management of chronic diseases such as asthma, since nonadherence to self-management medication is very common among asthmatics, in an effort to progress asthma management and achieve optimistic health outcomes, Lung Association of Saskatchewan has employed an intervention plan to provide an effective and enhanced quality asthma education for asthmatics patients and the health care providers, along with encouraging access to spirometer instruments [6].…”
Section: Introductionmentioning
confidence: 99%